Application of discovery learning model to improve learning outcomes in materials of changing objects in class V - Hamela Sari Sitompul; Idawati Situmorang; Yumitra Falenthine Br Ginting (Cendikia : Media Jurnal Ilmiah Pendidikan, 2023)
The learning process must be able to create fun learning situations (joyful learning) and encourage students to actively learn and think creatively. The product aspect refers to whether learning is able to achieve its goals, namely improving students' abilities according to the specified standard of ability and competence, in this case reflected in student learning outcomes. This study aims to improve student learning outcomes in the matter of changing the shape of objects through the application of the discovery learning model to fifth grade students at SD Negeri 094147. This type of research is classroom action research (PTK) which is carried out in two cycles. The subjects of this study were 25 students of class V SD Negeri 094147. Data collection techniques used are tests, observation and documentation. The data analysis technique was carried out in a quantitative descriptive manner. The results showed that there was an increase in learning outcomes, during the pre-action, the class average was 65.76 for completeness there were 12 students or 48% and incomplete there were 13 students or 52%. This result does not meet the KKM, namely 70.00. In cycle I, there was an increase in class average results of 71.92, there were 15 students or 60% completeness and there were 10 students or 40% incomplete, meaning there was an increase in the pre-action average score to cycle I of 6.16, while cycle II the results experienced another increase, namely the class average increased to 76.90 and completeness was 22 students or 88% and incomplete there were 3 students or 12%, thus there was an average increase from cycle I to cycle II of 4.98. In addition, the activeness of students in following the lessons also increased. This is indicated by the increasing activeness of students in asking questions, answering questions and expressingopinions.